From the monologue to the dialogue of knowledge? An epistemological and pedagogical reflection on the incorporation of traditional Indigenous knowledge within Mexico´s intercultural education system - Rosa, Carlo (Education Policy Analysis Archives, 2021)
This article analyzes the concept of the dialogue of knowledge in intercultural education. The analysis centers on three points: the theoretical difficulties in reconciling inclusion and dialogue; the debate surrounding the pertinence of the methods and instruments of Western epistemologies for systematizing indigenous forms of knowledge; and the critique of the proposed incorporation of indigenous knowledge into the curricular design of indigenous education and education for migrants. I argue that the Mexican education system, which remains immersed in an inclusivist and homogenizing ideology, has yet to evolve from a cultural, pedagogical, and epistemological monologue toward a dialogue of knowledge. The article concludes that the main challenge consists in achieving the ideal of an intercultural education for all, specifically regarding the indigenous education system, through promoting epistemological debates surrounding indigenous forms of knowledge. Such a process is necessary to avoid erroneous systematization processes and achieve the incorporation of indigenous knowledge within school curricula.